Lignin-Derived Carbon Coated Nanoscale Zero-Valent Iron as a Novel Bifunctional Material for Efficient Removal of Cr(Vi) and Organic Pollutants - Sanchez-Poblete, J (ELSEVIER, 2022)
Efficient removal of heavy metal ions and organic pollutants in wastewater is of great significance to healthy development of ecosystems. However, the facile preparation of novel functional materials for robust removal of both types of contaminants still remain a challenge. Herein, bifunctional composites derived from nanoscale zero-valent iron (nZVI) coated with lignin-derived carbon (LC) were fabricated via a carbothermal reduction strategy and denoted as Fe-0@LC. This hybrid material exhibits superior performance with a maximum heavy metal removal amount of Cr(VI) as high as 575.4 mg/g from aqueous solutions. Notably, the elimination rate of Cr(VI) (100 mg/L) by F-0@LC could reach up to 100% through adsorption and reduction. Furthermore, the obtained Fe-0@LC occurs Fenton-like reactions without additional supply of H2O2 toward effective degradation of organic pollutants, including 100%, 100% and 80% for methylene blue, methyl orange and congo red, respectively. The in-depth experimental and theoretical analyses reveal the synergistic effects between the catalytic Fe0 center and the lignin-derived carbon boost the activity for catalytic degradation of organic dyes and Cr(VI) in the optimized conditions. This work not only provides critical insights into rational design, working mechanism, and application of bio-functional materials for wastewater treatment, but also achieves the goal of "treating waste with waste ".